The Influence of Facilities and Competencies on The Performance of The State Civil Apparatus of North Langowan District Office - Emor, Syanty Hesly; Masengi, Evi Elvira; Kairupan, Sisca Beatrix (Technium Social Sciences Journal, 2023)
This research aims to test whether there is a correlation and influence between: a) Facilities (X1) and Performance (Y); b) Competency (X2) and Performance (Y); c) Facilities (X1) and Competence (X2) simultaneously with Performance (Y). The research method used was a quantitative method with a total of 30 respondents. Data analysis used the SPSS IBM 24 program. The results showed that there was a correlation between 1) Facilities (X1) and performance (Y), 2) competence (X2) and performance (Y) and, 3) Facilities (X1) and competence (X2) simultaneously with the performance of (Y) State Civil Apparatus North Langowan District Office. Then the test results to find the significance of the influence obtained the results that 1) there is no significant influence between Facilities (X1) on Performance (Y), 2) Competence (X2) has a significant effect on Performance (Y), and 3) Facilities (X1) and Competency (X2) simultaneously influences the Performance (Y) of the State Civil Apparatus of North Langowan District Office.